PENGARUH PERSEPSI KESESUAIAN, SISTEM INTERNAL KONTROL, DAN PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KECURANGAN AKUNTANSI PADA PT. BANK PERMATA, TBK - Prafitri Ahma; Reza Hanafi Lubis (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2022)
Accounting fraud is a misstatement or intentional omission of amounts or disclosures in financial statements to deceive users of financial statements and misstatements arising from improper treatment of assets (often referred to as misappropriation or embezzlement) related to the theft of entity assets that result in financial statements not being presented. in accordance with generally accepted accounting principles in Indonesia. This study aims to determine the effect of perceived conformity, internal control systems and also the implementation of good corporate governance at PT Bank Permata, Tbk. The method used in this study is a quantitative method, with a sample of 38 out of 51 all employees of PT Bank Permata, Tbk who serve as administration/finance, marketing, customer service and teller. The type of data used is primary data. The results showed that partially the perceived facility suitability variable had no effect on the accounting fraud variable. The internal control system variable has a partial effect on the accounting fraud variable. The good corporate governance variable partially has no effect on accounting fraud. And simultaneously the variables of conformity perception, internal control system and good corporate governance have an effect on accounting fraud